A High‐Performance Li–O2 Battery with a Strongly Solvating Hexamethylphosphoramide Electrolyte and a LiPON‐Protected Lithium Anode. Issue 30 (6th June 2017) - Zhou, Bin; Guo, Limin; Zhang, Yantao; Wang, Jiawei; Ma, Lipo; Zhang, Wen‐Hua; Fu, Zhengwen; Peng, Zhangquan
Abstract : The aprotic Li–O2 battery has attracted a great deal of interest because theoretically it can store more energy than today's Li‐ion batteries. However, current Li–O2 batteries suffer from passivation/clogging of the cathode by discharged Li2 O2, high charging voltage for its subsequent oxidation, and accumulation of side reaction products (particularly Li2 CO3 and LiOH) upon cycling. Here, an advanced Li–O2 battery with a hexamethylphosphoramide (HMPA) electrolyte is reported that can dissolve Li2 O2, Li2 CO3, and LiOH up to 0.35, 0.36, and 1.11 × 10 −3 m, respectively, and a LiPON‐protected lithium anode that can be reversibly cycled in the HMPA electrolyte. Compared to the benchmark of ether‐based Li–O2 batteries, improved capacity, rate capability, voltaic efficiency, and cycle life are achieved for the HMPA‐based Li–O2 cells. More importantly, a combination of advanced research techniques provide compelling evidence that operation of the HMPA‐based Li–O2 battery is backed by nearly reversible formation/decomposition of Li2 O2 with negligible side reactions. Abstract : A high‐performance Li–O2 battery is realized by employing a strongly solvating hexamethylphosphoramide (HMPA) electrolyte that can effectively dissolve Li2 O2 and a LiPON‐protected lithium anode that can be reversibly cycled in HMPA electrolyte. A combination of advanced research techniques provide compelling evidence that operation of the HMPA‐based Li–O2 battery is backed by nearly reversible formation/decomposition of Li2 O2 with negligible side reactions.